Wykorzystanie outsourcingu usług informacyjnych w działalności banków spółdzielczych - Janc, Alfred; Kotliński, Grzegorz (Service Outsourcing in the Business of Co-Operative Banks, 2005)
The European and world financial market is created by two main factors: European integration and information technology that lead to the development of e-commerce. Both of them affect Polish co-operative banking sector. Nowadays, it is necessary for co-operative banks to invest in new technology. Investing in IT is determined by law regulations and the need to create modem, competitive banking services. The paper presents some results of the research into IT application in Polish co-operative banks.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1068, s. 72-90